'The machine being set in motion': the automaton chess-player in urban and literary culture, 1839–1851. Issue 2 (3rd April 2021) - Sharples, John
ABSTRACT: This article examines nineteenth-century chess-player and writer George Walker's essay 'Anatomy of the Chess Automaton' (1839). Walker's writing frequently highlighted how spaces of urban modernity co-existed uneasily with historical memories. His tendency to highlight disreputable scenarios regarding chess-play can be set against a narrative which suggests chess-play became respectable in the mid-to-late nineteenth century. Unusually for Walker, however, his 'Anatomy of the Chess Automaton' demonstrates a desire to close off meaning and complexity, to diminish the potential for disreputable acts, whilst existing at odds with the historical context in which he wrote. This cultural mode in which Walker operated in can be viewed through the conceptual frameworks of curiosity (following Barbara M. Benedict) and respectability (following Mike Huggins) which highlight ideas of regulation, consumption, performance, transgression, and ambition. This article employs the frameworks of curiosity and respectability to interrogate related leisure and sporting practices in relation to the Automaton Chess-Player which existed outside the regular boundaries of society. It continues research previously published in Sport in History and elsewhere on the nature of chess-play and chess-spectacle as a disreputable spectacle. Ultimately, I show how both Walker and the object of his essay were curiosities themselves, engaging in an infinite game which produced a jumble of meanings.